Effect of heater orientation on pool boiling heat transfer from sintered copper microporous coating in saturated water. (December 2016) - Jun, Seongchul; Kim, Jinsub; You, Seung M.; Kim, Hwan Yeol
Highlights: The effect of orientation on pool boiling experiment on a sintered microporous coating was conducted for water. The CHF decreased as inclination angle increases at downward directions. The CHF enhancement on the microporous coating was up to 4.5 times compared to that of a plain surface. Abstract: In this study, we investigate the heater orientation effects at inclination angles from 0° (horizontal upward) to 180° (horizontal downward) on pool boiling heat transfer of saturated water using a durable high-temperature thermally-conductive microporous coating (HTCMC) created by sintering copper powder of an average particle size of 67 μm onto a 1 cm × 1 cm plain copper surface with ∼300 μm thickness. The HTCMC surface showed a critical heat flux (CHF) of ∼2 MW/m 2 and a maximum nucleate boiling heat transfer (NBHT) coefficient of ∼400 kW/m 2  K, which are 2 and 8 times higher than those of a plain copper surface, respectively, at the upward horizontal inclination angle. The current experimental results showed that the CHF values of the HTCMC were maintained as ∼2 MW/m 2 at upward inclination angles from 0° to 90°, whereas the CHF values decreased as the inclination angle changed from 90 o to 180 o, at which point the values were ∼1.4 MW/m 2 . The reduction at 180° is due to individual bubbles merging and forming larger bubbles by blockage from the surface. This increases the vapor residence time on the surface and prevents liquid access to the heated surface at downward inclination angles. However, it is noted that the CHF value of the HTCMC at 180° is ∼4.5 times higher than that of plain copper surface (0.3 MW/m 2 at 180°). HTCMC also shows a noticeably higher CHF value at 180° compared to nanocoating or other enhanced surfaces. This significant CHF enhancement is believed to be due to a large number of small feed jet bubbles created from porous structures, postponing the dryout caused by forming large bubbles on the heated surface.